ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT DARI MAKANAN TRADISIONAL SUKU REJANG DI PROVINSI BENGKULU: “LEMEA” - Moga Kurnia; Hermansyah Amir; Dewi Handayani (ALOTROP, 2020)
This study aims to specify the genus of lactic acid bacteria (LAB) in "lemea" and measure the activity of LAB isolates in producing lactic acid. The sample "lemea" came from one of the home industries in Daspetah Village, Ujan Mas District, Kepahiang Regency which was fermented for 7 days. The research was conducted from February to May 2019, at the Learning Laboratory of Biology and Chemistry, Faculty of Teacher Training and Education, University of Bengkulu. Isolation of LAB from "lemea" using selective media De Man, Rogosa and Sharpe (MRS) supplemented with 0.5% CaCO3 using the pour plate method. The steps of this study include, sampling "lemea", isolation of LAB, identification of macroscopic and microscopic bacteria (Gram staining) and determining% of lactic acid levels using the titration method to measure the activity of LAB isolates. The results identification of BAL isolates in "lemea" obtained two LAB isolates with codes of LK1 and LK2 isolates that had cocci, Gram positive and did not have spores. The measurements results of LAB activity in producing lactic acid, for LK1 isolates, obtained lactic acid levels of 1.92% while LK2 isolates were 1.56% of the local mass. According to the results identification,LK1 and LK2 isolates are the genus Leuconostoc and the highest activity in producing lactic acid in LK isolates.